KEBIJAKAN PENGEMBANGAN WISATA PANTAI KENJERAN SURABAYA DAN KONFLIK NELAYAN - Amal Taufiq; Siti Azizah (UNIVERSITAS SEBELAS MARET (UNS), 2020)
The focus of this research is the conflict that occurred between the the fishermen of Tambak Wedi Kenjeran Surabaya and PT PP Properti Suramadu, which represents the Surabaya city government as a result of government policies in developing the Kenjeran Beach tourism area, especially in the cable car development plan. This study used a qualitative approach, so that in the data mining technique the researcher used the method of observation, in-depth interviews, and documentation. From the research results, it was found that the Kenjeran beach tourism development policy carried out by the Surabaya City Government was in accordance with the natural and socio-cultural potential of the local community, but the impact of this policy was a conflict which in Ralf Dahrendorf's perspective there were three groups involved in the conflict. namely quasi groups, interest groups and conflict groups. The conflict started because of the demolition of a fishing post which had been used to monitor boats, three posts were dismantled, a fishing post for cumi-cumi group, kakap merah group and dorang groups, due to massive protests from fishermen until finally there was mediation by the Surabaya legislative, finally a fishing post was built. reset at the same location.Keywords: Tourism Area Development, Government Policy, Fishermen AbstrakFokus dalam penelitian adalah konflik yang terjadi antara nelayan Tambak Wedi kecamatan Kenjeran Surabaya dengan PT PP Properti Suramadu yang mewakili pemeritah kota Surabaya sebagai dampak dari kebijakan pemerintah dalam pengembangan kawasan wisata Pantai Kenjeran terutama dalam rencana pembangunan Kereta Gantung. Penelitian ini menggunakan pendekatan kualitatif, sehingga dalam teknik penggalian data peneliti menggunakan metode observasi, wawancara mendalam, dan dokumentasi. Dari hasil penelitian ditemukan bahwa kebijakan pengembangan kawasan wisata pantai Kenjeran yang dilakukan oleh Pemerintah Kota Surabaya sesuai dengan potensi alam dan sosial budaya masyarakat setempat, namun dampak dari kebijakan itu terjadi konflik yang dalamk persepektif Ralf Dahrendorf ada tiga kelompok yang terlibat dalam konfik itu. yaitu kelompok semu, kelompok kepetingan dan kelompok komflik. Konflik dimulai karena adanya pembongkaran pos nelayan yang selama ini digunakan untuk memantau perahu, ada tiga pos yang dibongkar, pos nelayan kelompok cumi-cumi, kakap merah dan dorang, karena protes masif dari nelayan hingga akhirnya ada mediasi oleh DPRD Surabaya, akhirnya pos nelayan dibangun ulang di lokasi yang sama.Kata Kunci : Wisata Pantai; Kebijakan Pemkot; Nelayan